Relationship of thyroid peroxidase antibody test with abnormal thyroid function tests (Journal of Pathology of Nepal, 2017)
Background: Autoimmune thyroid disease results from a complex interaction between genetic and enviromental factors. The aim of this study was to find association of anti-thyroid peroxidase antibody with abnormal thyroid function tests. Materials and Methods: This is a retrospective  study, conducted in 160 patients who showed abnormal thyroid function tests  in grande city clinic and hospital services and Kantipur dental college  for  duration  of 18 months since Baisakh 2072.Results: Among 160 individuals , 126(78.8%) were female and 34(21.2%) were male. Subclinical hypothyroidism (56.3%) were most common than overthyperthyroidism (18.0%), overthypothyroidism (16.9%) and subclinical hyperthyroidism (8.8%). Anti thyroid peroxidase antibodies test  was shown positive in  102/160 (63.8% ) cases.Conclusion: According to the present study, anti- thyroid peroxidase antibody has been significantly associated with thyroid dysfunction, it can be used as diagnostic marker for thyroid autoimmune diathesis.